Prevention of Early Age Marriage in Realizing a Superior Generation Z in MA Bilingual Entrepreneurship Robhitotul Ashfiya, Gresik - Velayati, Naili; Fathoni, Achmad; Hikmah, Maziyyatul (LPPM Universitas Yudharta Pasuruan, 2025)
The high rates of early marriage and divorce in Gresik Regency reflect the low awareness among adolescents regarding the importance of education and readiness for family life, which negatively impacts the quality of the younger generation, particularly Generation Z. This study aims to analyze strategies for preventing early marriage at MA Billingual Entrepreneurship Robithotul Ashfiya through educational and socialization approaches, as well as by strengthening students’ entrepreneurial skills and financial literacy. The research employed a Participatory Action Research (PAR) method, actively involving teachers, students, and parents in problem identification, interactive seminars, group discussions, and understanding evaluation. The findings indicate that counseling activities and skill reinforcement significantly increased students’ awareness of the risks associated with early marriage and the importance of continuing education. The implication is that madrasahs can play a strategic role as agents of change in shaping an empowered and competitive young generation, prepared to face future challenges by delaying marriage until reaching a mature age.